Penerapan Enterprise Risk Management (ERM) dalam menurunkan risiko keuangan bank syariah - Aulya, Mimma Alif (Maliki Interdisciplinary Journal, 2025)
Enterprise Risk Management (ERM) is an integrated approach designed to comprehensively manage various types of financial risks within Islamic banks. In the face of digitalization, market competition, and global economic uncertainty, Islamic banks are required to establish effective risk management systems that comply with Sharia principles. ERM involves the processes of identifying, measuring, monitoring, and controlling risks such as credit, liquidity, market, operational, compliance, return, and investment risks. The comprehensive implementation of ERM helps Islamic banks strengthen internal control systems, prevent fraud, and maintain financial stability and operational sustainability. In addition, ERM supports the enhancement of good corporate governance and fosters greater trust from regulators and customers. This study emphasizes that ERM is not only a risk mitigation tool but also a critical foundation for building a resilient, transparent, and trustworthy Islamic banking system. Through ERM, Islamic banks are better equipped to respond adaptively to the complexity of financial risks, ensuring that their role as trustworthy financial institutions committed to the public good continues to thrive and evolve.